Kritik Psikologi Sastra Tokoh Utama Dalam Naskah Drama Abadi Sepanjang Malam Karya Max Arifin - Ridayani Ridayani; Dessy Saputry; Rindi Nathasya; Amida Khoirotunnisa (Jurnal Pendidikan Indonesia (JOUPI), 2023)
This research discusses Sigmund Freud's psychoanalytic studies. The aim of this research is to analyze literary psychology in the drama Storm All the Night. This research uses a qualitative descriptive research method. The qualitative descriptive method is a method for describing something. This method is used to explain the overall results of the analysis that has been carried out, the results of which are in the form of words or words from what has been observed. The object that is the focus of this research is the inner conflict of the main character in the drama Storm Throughout the Night by Max Arifin. The results of this research are the existence of inner conflict in the form of id, ego and superego in drama scripts.